The genus Drymeia Meigen, 1826 (Diptera: Muscidae) in Kyrgyzstan: new records and new species - Sorokina, Vera S. (European journal of taxonomy)
The muscid genus Drymeia Meigen, 1826 in Kyrgyzstan has been studied. One new species is described: Drymeia ziegleri sp. nov. An annotated checklist and keys for each sex of the six named species of Kyrgyzstan Drymeia are provided. Five species are newly recorded from Kyrgyzstan. An image of the new species is given.